Causes and Outcome of Neurogenic Vision Loss - Ghimire, Pukar; Karn, Ragesh; Gajurel, Bikram Prasad; Ojha, Rajeev; Rajbhandari, Reema; Shahi, Sumit; Panthee, Pradeep; Bhandari, Pragya; Lamichhane, Jayaram (Journal of Nepal Health Research Council, 2024)
Background: Neurogenic vision loss is often a medical emergency. Early evaluation and urgent treatment of the causes is the key to better visual prognosis. Methods: This was a retrospective cross-sectional study based on hospital records of patients admitted to the Neurology department of Tribhuvan University Teaching Hospital with complain of diminution of vision from April 2023 to March 2024. The visual outcome of the patients was recorded based on telephone interviews with the patients or their family members. Results: A total of 64 patients were identified of which 62 were interviewed for visual outcome. The median age was 38 years of which 62.5% were female. Bilateral eye involvement was reported in 59.4% of the cohort and half of the patients had normal optic disc. The distribution of visual acuity at presentation was 39.1% for 6/60 or better, 9.4% for 3/60 to less than 6/60, 32.8% for 3/60 and 18.8% having no perception of light. The commonest diagnosis in decreasing order of frequency was idiopathic intracranial hypertension, neuromyelitis optica spectrum disorder, idiopathic optic neuritis and myelin oligodendrocyte glycoprotein antibody disease with the frequency being 17.2%, 15.6%, 10.9% and 9.4% respectively. Of 62 patients interviewed, 67.7% reported a complete recovery of vision, 14.5% reported a partial recovery and 17.8% reported no visual recovery. Severity of visual loss at presentation was associated with poor visual outcome (p=0.021) whereas age, gender, number of eyes affected and duration of visual symptoms had no significant relation to visual recovery. Conclusions: Idiopathic intracranial hypertension, neuromyelitis optica spectrum disorder, Idiopathic optic neuritis, myelin oligodendrocyte glycoprotein antibody disease were the commonest causes of neurogenic visual loss. The severity of visual loss at onset is a prognostic marker of the visual recovery in these patients. Keywords: Blindness; Vision Disorders; Optic Nerve Diseases; Neural Optical Lesion